Procedury związane z wprowadzeniem stałego diakonatu w diecezjach polskich - Jakubiak, Tomasz (Prawo Kanoniczne, 2010)
Permanent Deaconship received without intention of future priesthood has been known since the beginning of the Church. Sixth century turned out to be a crucial moment in the history of Deaconship. That’s then when in the Western Church because of various reasons it started to loose its importance. Vaticanum II tried to change the way it was perceived. Together with promulgation of the norms contained in the Code of John Paul II part of the documents which had been promulgated earlier regulating this subject was canceled. After presenting most important documents issued by the Popes, Congregations and Conference of Polish Bishops together with explanations, the author focuses on the most important actions undertaken by Diocese Bishops from the moment permanent Deaconship was accepted in the Diocese till the moment the newly ordained deacon is send for the service.